Analisa Tingkat Kenyamanan Pejalan Kaki Di Kota Tomohon - Mamuaja, Denny M. A.; Rompis, Semuel Y. R.; Timboeleng, James A. (JURNAL ILMIAH MEDIA ENGINEERING, 2018)
Tomohon City is one of the cities in North Sulawesi Province, Indonesia. Before 2003 was one of the subdistricts in Minahasa District. In his development, Tomohon experienced a lot of progress, so there is aspiration of its citizens to improve the status of Tomohon into a city. Tomohon became an autonomous region (city) with the enactment of Law Number 10 Year 2003 regarding the Establishment of South Minahasa Regency and Tomohon City in North Sulawesi Province by DPR RI, but the inauguration was only on August 4, 2003. To support the activity and development of Tomohon City needed infrastructure physically and non-physically available so as not to inhibit the process. Physical infrastructure that includes facilities and infrastructure, use, design, etc. and non-physical include social relations, economic activity, etc.      The need for physical infrastructure is essential to support the accessibility of urban activities and developments. The pedestrian lanes should be used only for pedestrian activity, not other activities such asvehicle activity and vehicle parking, trade because it can endanger safety and reduce the comfort of pedestrian circulation. Planning for pedestrian track requirements should be well planned in accordance with the rules andregulations of pedestrian path planning by considering and prioritizing safety and comfort aspects of pedestrians.       Another factor that is often added as a support for comfort is physical comfort. Physical comfort is closely related to the aspect of the suitability of the shape and the design of the objects or elements built into thesurrounding environment, such as the suitability of park benches, garden lights, pedestrian paths, billboards and other infrastructure. Physical comfort is often associated with the concept of "ergonomic", ie objects orstructures built dimensional and structural to follow the needs of human gestures users. It is intended that the object or structure built can be optimal and convenient for use by pedestrian pedestrian pedestrian users.      In addition to increasing knowledge and understanding the comfort level of pedestrian, the aims of this research are to . know the existing condition and supporting facilities of the pedestrian lane in the TomohonCentral Area is related to the convenience aspect of the users, to analize the perceptions and preferences of pedestrian lane users on the convenience of the pedestrian lane in the Tomohon Central Area, and to prepare some recommendations for improving the quality of services to function effectively and comfortably for pedestrian lane users and also expected to be applied to other pedestrian routes.Method used in this study are data sampling and stastistical analysis. Results revealed that  the dimension of the pedestrian lane in the Tomohon Central Area has met the minimum standard of a pedestrian track in urban areas, the calculation of the analysis of the main priority of the pedestrian line function in Tomohon City Centerregarding the  priority choice of function of pedestrian special path is quite good. From the description can be drawn the average conclusion that the perception of pedestrian pedestrian users, especially pedestrians generally feel quite comfortable in the utilization of pedestrian paths in Tomohon Central Area. Current conditions in the pedestrian path in the Tomohon City Center area in terms of convenience according to the theory of comfort as in the aspect of convenience itself is: the sun, the scenery in the pedestrian path, the clarity of circulation between pedestrians and other users, vehicle noise, aroma the safety of the  Aspects expected by respondents in terms to improve the convenience of pedestrian paths in the Tomohon City Center that is added shade trees to reduce the blazing sun. Keywords: comfort level of pedestrian, physical comfort, quality service, padestrianlane, special path